Pengaruh Model Pembelajaran Teams Games Tournament Termodifikasi Berbasis Outbound terhadap Prestasi Belajar Fisika Ditinjau dari Motivasi Belajar - Imam Abdul Syukur; Muhardjito –; Markus Diantoro (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2014)
The purpose of this study was to determine the influence of Teams Games Tournament learning model of modified outbound based on Physics learning achievement to students’ learning motivation. The type of the study was quasi-experimental in the form of 2x2 factorials. Subjects of the study are students of 10th grade of SMA Negeri 1 Nganjuk (Public Senior Secondary School). Three classes were randomly assigned as experimental models of modified Teams Games Tournament outbound based and three classes as conventional (control) classes. Instruments used consisting of data collection instruments and also treatment instrument. Hypothesis testing using two-way anova and Tukey test at 5% significance level. The results showed significant difference of achievements in learning physics among students who study using Teams Games Tournament learning model outbound based and conventional one. The results of the study also showed that there are interactions between model of learning and learning motivation towards learning achievements. Physics learning achievements of students who have high motivation, who learn using modified Teams Games Tournament learning model outbound based are not even higher than the conventional one. Whereas the physics learning achievements of students having low motivation who learn using modified Teams Games Tournament learning model outbound based, are higher than the conventional one. ABSTRAK Tujuan penelitian ini untuk mengetahui pengaruh model pembelajaran Teams Games Tournament termodifikasi berbasis outbound terhadap prestasi belajar Fisika ditinjau dari motivasi belajar siswa. Jenis penelitian kuasi eksperimen dalam bentuk faktorial 2x2. Subjek penelitian adalah siswa kelas X Sekolah Menengah Atas Negeri 1 Nganjuk. Secara acak ditetapkan tiga kelas eksperimen model Teams Games Tournament termodifikasi berbasis outbound dan tiga kelas sebagai kelas konvensional (kontrol). Instrumen yang digunakan terdiri atas instrumen pengumpulan data dan instrumen perlakuan. Pengujian hipotesis menggunakan Anava dua arah dan uji lanjut menggunakan uji Tukey pada taraf signifikansi 5%. Hasil penelitian menunjukkan adanya perbedaan yang signifikan antara prestasi belajar Fisika yang belajar dengan model pembelajaran Teams Games Tournament termodifikasi berbasis outbound dibanding konvensional. Hasil Penelitian juga menunjukkan ada interaksi antara model pembelajaran dan motivasi belajar terhadap prestasi belajar. Prestasi belajar fisika siswa yang memiliki motivasi tinggi, yang belajar dengan model pembelajaran Teams Games Tournament termodifikasi berbasis outbound tidak lebih tinggi dari konvensional, sedangkan siswa yang mempunyai motivasi rendah, prestasi belajarnya lebih tinggi daripada konvensional.